2018
DOI: 10.1111/maps.13231
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Q to thermal metamorphism in parent bodies: Experimental simulation

Abstract: Planetary noble gases in chondrites are concentrated in an unidentified carrier phase, called “Q.” Phase Q oxidized at relatively low temperature in pure oxygen is a very minor part of insoluble organic matter (IOM), but has not been separated in a pure form. High‐pressure (HP) experiments have been used to test the effects of thermal metamorphism on IOM from the Orgueil (CI1) meteorite, at conditions up to 10 GPa and 700 °C. The effect of the treatment on carbon structural order was characterized by Raman spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…46 Verchovsky and coworkers have shown that Γ D increases with thermal alteration, where a larger D-to-G intensity ratio I D / I G suggests a reduction of the thermal alteration. 46…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…46 Verchovsky and coworkers have shown that Γ D increases with thermal alteration, where a larger D-to-G intensity ratio I D / I G suggests a reduction of the thermal alteration. 46…”
Section: Resultsmentioning
confidence: 99%
“…46–49 The D-band width ( Γ D ) has been reported to be more sensitive to thermal metamorphism than the G-band width ( Γ G ) and is considered a more accurate probe for the thermal history of the parent asteroid. 46 Verchovsky and coworkers have shown that Γ D increases with thermal alteration, where a larger D-to-G intensity ratio I D / I G suggests a reduction of the thermal alteration. 46…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations